The Role of Intestinal Bacteria and Gut–Brain Axis in Hepatic Encephalopathy - Chen, Zefeng; Ruan, Jingsheng; Li, Dinghua; Wang, Min; Han, Zhiwei; Qiu, Wenxia; Wu, Guobin (Frontiers in Cellular and Infection Microbiology, 2021)
Hepatic encephalopathy (HE) is a neurological disorder that appears in patients with liver insufficiency, and the pathogenesis remains unclear. Consequently, there are few effective diagnosis and treatment methods. Compared with healthy individuals, the intestinal flora of patients with liver disease is significantly different and is related to the occurrence of HE. Moreover, intestinal microflora is closely related to multiple links in the pathogenesis of HE, including the theory of ammonia intoxication, bile acid circulation, GABA-ergic tone hypothesis, and neuroinflammation, which contribute to cognitive and motor disorders in patients. Several pieces of evidence in both clinical and animal trials suggest that restoring the homeostasis of intestinal bacteria or providing specific probiotics has significant effects on neurological disorders of HE. Thus, the review aims to discuss the potential microorganism mechanisms and the metabolic effect play in the progression of HE, typical via the gut-brain axis and its potential role as a therapeutic target in HE.